Информационное право России: учеб. пособие / Н. Н. Ковалева - Ковалева Наталия Николаевна (Дашков и К°, 2007)
Экземпляры: СЭ (20071002) / Инвентарный номер: 1065588 / Цена: 196.57 / Сис.шифр: 67.401 / Авт.знак: К 56 / ГРНТИ: 10 / ББК: 67.401.114